A facile chemoenzymatic synthesis of SARS-CoV-2 glycopeptides for probing glycosylation functions. Issue 55 (18th June 2021) - Zong, Guanghui; Li, Chao; Prabhu, Sunaina Kiran; Zhang, Roushu; Zhang, Xiao; Wang, Lai-Xi
Abstract : Structurally well-defined synthetic SARS-CoV-2 glycopeptides provide useful probes for characterizing the glycan binding specificity of lectin and neutralizing antibody. Abstract : Glycosylation plays important roles in SARS-CoV-2 infection. We describe here a facile chemoenzymatic synthesis of core-fucosylated N -glycopeptides derived from the SARS-CoV-2 Spike protein and their binding with glycan-dependent neutralizing antibody S309 and human lectin CLEC4G. The synthetic glycopeptides provide tools for further functional characterization of viral glycosylation.